ENHANCING ENGLISH LANGUAGE LEARNING THROUGH TECHNOLOGY-INTEGRATED TEACHING: A TESOL PERSPECTIVE - Yuldoshova Farida (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: The landscape of English language education has undergone significant transformations in the contemporary era, characterized by rapid advancements in digital tools and technological platforms. The field of Teaching English to Speakers of Other Languages (TESOL) has responded to these changes by embracing an array of technology-integrated approaches designed to optimize the learning experience, facilitate language acquisition, and cater to the diverse needs of learners across different contexts. This article explores the theoretical and practical dimensions of technology integration in English language teaching, and it illuminates how such integration reshapes pedagogical strategies, learner autonomy, assessment practices, and professional development within the TESOL domain.